Picotamide Protects Mice from Death in a Pulmonary Embolism Model by a Mechanism Independent from Thromboxane Suppression - Gresele, Paolo; Corona, Cinzia; Alberti, Paolo; Nenci, Giuseppe G (Thrombosis and Haemostasis, 1990)
We have previously characterized the new antiplatelet agent picotamide as a dual thromboxane synthase inhibitor/thromboxane A2 receptor antagonist in human platelets. We have now studied the antithrombotic activity of this drug in a simple animal model of lung platelet thromboembolism in the mouse. Picotamide, given i. p. 1 hr before the thrombotic challenge, protected mice from death caused by the i. v. injection of collagen plus epinephrine in a dose-dependent way; the dose reducing mortality by 50% was 277 mg/kg while for aspirin it was 300 mg/ kg. Picotamide was also able to reduce the mortality provoked by the i. v. injection of the stable TxA2 mimetic U46619; BM 13.505, a pure TxA2-receptor blocker, was also effective while aspirin was totally inactive. Picotamide, finally, reduced the lethal consequences of the i. v. injection of a 12.5% suspension of hardened rat red blood cells, a model in which platelets are not involved; aspirin was totally ineffective in this model while nicardipine, a calcium channel blocker, was active. Picotamide did not inhibit the formation of TxB2 in serum at any of the doses tested (100 to 750 mg/kg i.p.) while it did enhance significantly PGI2-synthesis from mice aortae and, even more, from mice lungs. The i.v. administration of picotamide (250 mg/kg 2 min before the thrombotic challenge) lead to a strong inhibition of serum TxB2 (−84.6%) and was associated with a higher antithrombotic effectPicotamide (375 mg/kg) reduced also significantly the drop in the number of circulating platelets and the number of histologi-cally-detected lung thromboemboli provoked by i. v. collagen plus epinephrine; however, aspirin (300 mg/kg), although less effective against mortality, was more active than picotamide in this respect. Finally, the addition of aspirin (100 and 300 mg/kg) to picotamide (250 and 375 mg/kg) led to a better antithrombotic effect despite a strong inhibition of PGI2 synthesis. Our data show that picotamide prevents sudden death provoked in mice by platelet lung thromboembolism through a mechanism largely independent from eicosanoid synthesis and only partially dependent on platelet inhibition. This drug reduces also the lethal consequences of mechanical (platelet-independent) lung embolism. A direct vasodilatory action on pulmonary vessels might explain the protective effects of picotamide in this model.